Penyiraman Tanaman Cabai Otomatis Dalam Greenhouse Berbasis IoT Menggunakan Platform Thingspeak - Rozie, Fachrul; Chandra, Yudi; Usman, Syaifudin; Erwin, Erwin (entries, 2023)
The current era is experiencing rapid advancements, and people are expecting a tool or technology that can assist in various tasks, particularly in agriculture. Hence, technology has become a necessity for humans. This final project aims to create a device that automates the process of watering chili plants, which was originally done manually. Irrigation is a crucial activity in chili plant maintenance because these plants require an adequate water supply to carry out photosynthesis and meet their growth and development needs. This project is accomplished by utilizing waste from a tilapia fishpond to replace the use of clean water for irrigating chili plants. Simultaneously, fish waste is employed as additional fertilizer for the plants. At a temperature of 27°C, with soil humidity readings below 60%, the pump will activate. Conversely, the pump will turn off if one of the sensors' readings does not meet the specified conditions to activate the pump, namely if the temperature rises above 27°C or the soil humidity surpasses the chili plant's ideal value of 80%. However, in this device, the pump is set to turn off at 75% humidity to prevent excessive soil moisture.